ANALISA KINERJA POMPA PEMADAM KEBAKARAN P-8300 C DI PERTAMINA HULU MAHAKAM ( PHM ) LAPANGAN SENIPAH TERMINAL (STUDI KASUS DI PERUSAHAAN PT.PERTAMINA HULU MAHAKAM) - Heri Cahyono; Rachmasari Pramita Wardhani; Rissetridharma Simanjuntak (MECHA JURNAL TEKNIK MESIN, 2021)
A pump is a machine used to move uncompressed fluid from one place to another with a certain distance, from a low to a high place or move fluid from a low pressure place to a high pressure place. The purpose of this study is to determine the performance value of the centrifugal pump and the decline from the previous test by the manufacturer, as well as what factors influence it. Retrieval of data in the PT.PHM senipah field is a fire extinguisher pump P-8300 C by reading directly the existing parameters in the form of exhaust pressure (P) and the amount of flow in the exhaust channel (Q). The data is analyzed to get the value of head speed, head loss and total head so that the performance will be obtained. Key words: Centrifugal pump, working fluid, performance.